Pemasaran Bokar Melalui Unit Pengolahan Dan Pemasaran Bokar (UPPB) Sebagai Upaya Peningkatan Pendapatan Petani Dari Usahatani Karet Di Kecamatan Sembawa Kabupaten Banyuasin - Anggiani, Fitri; Kurniawan, Rahmat (Universitas Muhammadiyah Palembang, 2021)
Bokar Processing and Marketing Unit (Rubber Processing Material) hereinafter referred to as (UPPB) according to the Regulation of the Minister of Agriculture Number 38/PERMENTAN/0T.140/8/2008 article 1 paragraph 13 Bokar Processing and Marketing Unit is a business unit or business unit formed by two or more plantation groups as a place for providing technical guidance to planters, processing, temporary storage and marketing of bokar (rubber processing materials). This study aims to determine the role of UPPB in Sembawa District and the level of income differences received by farmers who sell bokarya to UPPB and non-UPPB. The data obtained were then analyzed descriptively qualitatively, income calculation and T-test were carried out. The results showed that the role of UPPB in marketing bokar by making a liaison between suppliers and farmers directly in marketing bokar as well as efforts to increase the income of rubber farmers. The average income of rubber farmers who market bokar through UPPB is Rp. 2,556,298.09 ha/month, while farmers who choose marketing through non-UPPB are Rp. 1,419,130,764 ha/month.